The application of a new oxidation mortar bar test to mixtures containing different cementing systems. (10th June 2018) - Guirguis, Bassili; Shehata, Medhat H.; Duchesne, Josée; Fournier, Benoit; Durand, Benoit; Rivard, Patrice
Highlights: The applicability of oxidation mortar bar test to cementing systems was investigated. Extended exposure of blends with metakaolin to oxidizing solution causes significant expansion of the paste. The use of SCMs reduces expansion through reducing the permeation of oxidizing agents into the samples. The effects of SCMs on reducing oxygen permeation through concrete under field exposure needs to be investigated. Abstract: The effects of different cementing systems on the expansion of mortars containing iron sulphide-bearing aggregate was studied. Using a recently developed oxidation mortar bar test, the results showed that cementing systems containing low-calcium fly ash, metakaolin, slag, high-sulphate resisting Portland cement, or low heat of hydration Portland cement could reduce the expansion by 50–85%. The main suggested mechanisms behind the reduced expansion is the more refined pore structure of samples with SCMs, and the reduced C3 A of low heat of hydration Portland cement. The refined pore structure reduces the permeation of the oxidizing solution into the samples. The similarity of this to penetration of oxygen into concrete under field exposure needs to be determined. Soaking the samples for >3 h in the oxidizing agent can produce excessive expansion – not related to oxidation of iron sulphide phases – in samples with cementing blends containing reactive alumina such as metakaolin.